Evaluation of skin hydration after exposition to the aqueous and hydroalcoholic bases and silicone emulsion - Fujimura, Andressa T. [UNESP] (2013)
Several dermocosmetic bases even without active substances, can increase the cutaneous hydration, resulting in a beneficial effect to the skin. The evidence and interpretation of possible hydration effect of formulations in the skin can be carried through by means of histopathological and histomorphometrical evaluation, a time that allows the analysis of the epithelial tissue, of dermis and also of the cellular characteristics. The objective of this research was to evaluate the skin hydration after exposition to the aqueous and hydroalcoholic bases and silicone emulsion. Swines had areas submitted to treatments during 15 days with three different formulations (F1 - aqueous gel, F2 - hydroalcoholic gel and F3 - silicone emulsion). By means of histometric and histopathological techniques were gotten the thickness of the epidermis and stratum corneum. Comparison of means was done using ANOVA followed by the Tukey test. The F1 provoked significant increase in the thickness of the epidermis. The formulaton F2 provoked significant reduction in the thickness of the epidermis and stratum corneum. F3 not presented significant difference in this structures. According to the study, the type of base chosen intervenes with the skin hydration.